42 An observation of the predictors of patient adherence and performance in a multidisciplinary regional cardiac rehabilitation programme. (17th July 2020) - Griffiths, Rebecca; Jones, Aled; Davies, Hannah; Mitra, Rito
Abstract : Introduction: Cardiac Rehabilitation (CR) comprises physical, psychological and medical interventions which together aim to reduce and reverse underlying cardiac disease, improve symptoms of cardiac disease and enhance functional status of participants. It is recommended internationally after acute coronary syndromes and reperfusion therapies as well as for patients with stable coronary artery disease. Despite clear evidence in favour of CR, participation remains low. We retrospectively analysed 7 years of demographic data from a regional multidisciplinary exercise-based CR programme in South Wales between 2011 and 2018. Factors that may predict compliance and improvement with CR were investigated. Methods: Standard UK criteria were used to recruit patients to the CR programme. Patients' perceived fitness level, resting heart rate (HR), resting blood pressure and walking distance were recorded before and after CR. Exercise prescription was based on functional capacity test findings (performed prior to commencing CR), British Association for Cardiovascular Prevention and Rehabilitation risk stratification and functional ability. Patients worked at a moderate intensity, determined by observing their HR (40-70% HR reserve) and their rate of perceived exertion (12-14 on the Borg 6-20 scale). Aerobic exercise time was increased, and active recovery time reduced, as patients progressed through the CR programme. Results: 1288 patients were included in the analysis. 91.7% of the study population (n=1181) started the CR programme. Males were more likely to engage with the CR programme than females (p=0.02) although the proportion of patients starting CR was high in both groups (93% male, 88% female). Patients with atrial fibrillation (AF) were less likely to engage with CR (p<0.001). Of those that started CR, 67.3% completed the exercise programme (n=795). Younger patients were less likely to complete the CR programme than older patients (p<0.001). Linear regression modelling found that increasing age (p<0.001) and the presence of AF (p=0.05) reduced the improvement in walking distance. The presence of severely impaired left ventricular (LV) function did not influence the improvement in walking distance at the 0.05 significance level. Conclusions: Fewer females were referred and started CR than males in our programme. Although this discrepancy could represent a true gender difference in CR requirement, it may also represent under-referral of females to CR or indicate barriers to uptake of CR for females. Targeted work to encourage female participation in CR is clearly required to address this gender gap. Younger patients were more likely to drop-out of our CR programme than older patients. Retention of younger patients needs to be encouraged in future CR programmes as these patients have been shown to benefit from CR over a wide range of areas (1). Increasing age and presence AF, but not presence of severely impaired LV function, predicted poorer performance in CR. Reference: Rodrigues P, et al . Cardiac rehabilitation: does age matter? European Heart Journal 1 August 2013;34(suppl_1) :P5792. Conflict of Interest: Nil